Genetic inheritance of ornamental components in pepper plants (Capsicum annuum L.) (Acta Scientiarum. Agronomy, 2024)
Limited information is available regarding the genetic inheritance of ornamental traits in peppers (Capsicum spp.), which is crucial for enhancing these plants for ornamental purposes in breeding programs. This study aimed to elucidate the genetic inheritance of ornamental traits in segregating populations of pepper plants (C. annuum L.) from distinct parents and to characterize them based on their flowering and fruiting cycles. The selected parents, UNI01 and UNI05, were sourced from the active germplasm bank of Universidade Estadual de Montes Claros, Janaúba, Minas Gerais State, Brazil. The experiment took place in a greenhouse, involving manual hybridization between UNI01 and UNI05 to obtain seeds of segregating populations, which included F1, RC1, RC2, F2, and F3 generations. Qualitative traits assessed included flower corolla color, immature fruit color, and shapes of longitudinal and transversal fruit sections. Quantitative traits encompassed mean flowering and fruiting days. We employed chi-square tests (Ï‡²) to evaluate segregation patterns. The descriptor "corolla color" exhibited codominance, with a white corolla and purple borders linked to heterozygous genotypes. Dominant inheritance controlled the color of immature fruits, primarily purple. Genetic inheritance for transversal and longitudinal fruit shapes remained unexplained in the tested segregations. Parental and segregating generations displayed similar flowering and fruiting cycles. These results provide valuable insights for future breeding programs aimed at using this species for ornamental purposes.